University of Florida Potato Variety Trials Spotlight: ‘Adirondack Blue’ - Rodrick Z. Mwatuwa; Christian T. Christensen; Lincoln Zotarelli; Pam Solano (EDIS, 2017)
Explains the results of the trials and describes the cultivars. Published by the Horticultural Sciences Department.by Rodrick Z. Mwatuwa, Christian T. Christensen, Pam Solano, and Lincoln Zotarelli http://edis.ifas.ufl.edu/hs1293